2001
DOI: 10.1002/1097-0142(20010225)93:1<68::aid-cncr9009>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry in the differential diagnosis of serous effusions

Abstract: BACKGROUND The distinction between pleural mesothelioma (MS), reactive mesothelium (RM), and adenocarcinoma (AC) in serous effusions continues as a diagnostic problem in pathology. Immunohistochemistry can help, especially in surgical samples, but the optimum panel of antibodies has yet to be reported. The application of these antibodies to serous effusions has displayed variable results. The aim of this study was to evaluate the usefulness of eight monoclonal antibodies in the differential diagnosis of MS, RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Analysis of E‐cadherin expression in malignant effusions from patients with gastric and pancreatic carcinoma showed reduced expression of this adhesion molecule in the majority of specimens 53. In contrast, three recent studies showed frequent expression of this molecule in carcinoma cells of various origins (breast, lung, ovary, gastrointestinal tract) in effusions 15, 54, 55. It is interesting to note that an analysis of 4 breast carcinoma effusions showed staining in < 10% of cells in all specimens 54.…”
Section: Discussionmentioning
confidence: 97%
“…Analysis of E‐cadherin expression in malignant effusions from patients with gastric and pancreatic carcinoma showed reduced expression of this adhesion molecule in the majority of specimens 53. In contrast, three recent studies showed frequent expression of this molecule in carcinoma cells of various origins (breast, lung, ovary, gastrointestinal tract) in effusions 15, 54, 55. It is interesting to note that an analysis of 4 breast carcinoma effusions showed staining in < 10% of cells in all specimens 54.…”
Section: Discussionmentioning
confidence: 97%
“…Although ovarian cancer patients have the highest percentage of malignant peritoneal cytology, which represents the clinical stage, intraperitoneal metastasis and patient survival, the number of the patient specimens was small and insufficient (Khoury 1990;Ordoñez 1998a;Lozano et al 2001;Attanoos et al 2002). Furthermore, these studies examined only serous type but not other histological types of ovarian carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to apply immunocytochemical staining in the differentiation of these two types of cells. However, large differences exist in the results of these published studies, regarding both the value of some of the markers and which markers should be included in the routine diagnostic panel for differentiating them (Delahaye et al 1997;Fetsch et al 1998;Ordoñez 1998;Lozano et al 2001;Attanoos et al 2002). In addition, previous studies examined only serous type but not other histological types of ovarian carcinoma cases.…”
Section: Methodsmentioning
confidence: 99%
“…Ber-EP4 is a monoclonal antibody that identifies 34-kD and 39-kD cell surface glycoproteins present on the membrane of human epithelial cells but not on reactive or malignant mesothelial cells [9]. An increasing number of studies have shown the ability of this antibody to be a marker in the differential diagnosis of MAC from MM/RM [1], [10]–[37].…”
Section: Introductionmentioning
confidence: 99%